Adsorptive Removal of Zn(II) Ion from Aqueous Solution using Rice Husk-Based Activated Carbon - Taha, Mohd Faisal (American Institute of Physics, 2012)
The study of rice husk-based activated carbon as a potential low-cost adsorbent for the removal of Zn(II) ion from aqueous solution was investigated. Rice husk, an agricultural waste, is a good alternative source for cheap precursor of activated carbon due to its abundance and constant availability. In this work, rice husk-based activated carbon was prepared via chemical treatment using NaOH as an activation agent prior the carbonization process. Three samples, i.e. raw rice husk, rice husk treated with NaOH and rice husk-based activated carbon carbonized at 650oC, were analyzed for their morphological characteristics using field-emission scanning electron microscope/energy dispersive X-ray (FESEM/EDX). Other analyses were also conducted on these samples using fourier transmitter infrared spectroscopy (FTIR), CHN elemental analyzer and X-ray diffraction (XRD) for characterization study. The porous properties of rice husk-based activated carbon were determined by Brunauer-Emmett-Teller (BET) surface area analyzer, and its surface area and pore volume were found to be 255 m2/g and 0.17 cm2/g, respectively. The adsorption studies for the removal of Zn(II) ion from aqueous solution were carried out as a function of varied contact time at room temperature. The concentration of Zn(II) ion was analyzed using atomic absorption spectrophotometer (AAS). The results obtained from adsorption studies indicate the potential of rice husk as an economically promising precursor for the preparation of activated carbon for removal of Zn(II) ion from aqueous solution.